2022
DOI: 10.21203/rs.3.rs-1317086/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of the divergence characteristics of a jet transport aircraft wing using numerical method.

Abstract: The goal of the present paper work is to demonstrate the use of numerical matrix iteration technique to obtain the divergence speed of a jet transport aircraft wing by employing aerodynamic strip theory. Aerodynamics strip theory is employed to obtain the divergence speeds for a finite (Three Dimensional) wing and for an infinite (Two dimensional) wing by matrix iteration technique. The aircraft wing is divided in to a number of Multhopp’s stations. The elastic property of the wing of a typical jet transport i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The dynamic pressure q d with the least Eigen value, which is derived from equilibrium equation in its homogeneous-integral form, are used to calculate the torsional divergence speed of a 3-D wing [5]. Equation (20)'s homogeneous form is:…”
Section: Matrix-solution Methods Based On Strip Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…The dynamic pressure q d with the least Eigen value, which is derived from equilibrium equation in its homogeneous-integral form, are used to calculate the torsional divergence speed of a 3-D wing [5]. Equation (20)'s homogeneous form is:…”
Section: Matrix-solution Methods Based On Strip Theorymentioning
confidence: 99%
“…Experiments on airplane structures demonstrated that, within certain limitations, force and deflection are linearly connected. Even if the material that makes up the wing structure is stressed at a low level, elastic buckling in the skin of an aircraft wing structure can cause a discontinuity in the force deflection diagram [5]. As a result, the wing structure's elastic properties are presented in the range under the elastic buckling point.…”
Section: Structure Properties Of the Wingmentioning
confidence: 99%
See 3 more Smart Citations